Glocal Narratives of Resilience - Fraile Marcos, Ana Ma. (Ana María) (Milton : Routledge, 2019)
Resilience discourse has recently become a global phenomenon, infiltrating the natural and social sciences, but has rarely been undertaken as an important object of study within the field of the humanities. Understanding narrative in its broad sense as the representation in art of an event or story, Glocal Narratives of Resilience investigates the contemporary approaches to resilience through the analyses of cultural narratives that engage aesthetically and ideologically in (re)shaping the notion of resilience, going beyond the scales of the personal and the local to consider the entanglement of the regional, national and global aspects embedded in the production of crises and the resulting call for resilience. After an introductory survey of the state of the art in resilience thinking, the book grounds its analyses of a wide range of narratives from the American continent, Europe, and India in various theoretical strands, spanning Psycho-social Resilience, Socio-Ecological Resilience, Subaltern Resilience, Indigenous survivance and resurgence, Neoliberal Resilience, and Compromised Resilience thinking, among others, thus opening the path toward the articulation of a cultural narratology of resilience.
12 Lies and Reparation: Palliative or PoisonContributors; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Resilience (Personality trait); Personality in literature